2020
DOI: 10.3390/metabo10060253
|View full text |Cite
|
Sign up to set email alerts
|

A Metabolic Perspective and Opportunities in Pharmacologically Important Safflower

Abstract: Safflower (Carthamus tinctorius L.) has long been grown as a crop due to its commercial utility as oil, animal feed, and pharmacologically significant secondary metabolites. The integration of omics approaches, including genomics, transcriptomics, metabolomics, and proteomics datasets, has provided more comprehensive knowledge of the chemical composition of crop plants for multiple applications. Knowledge of a metabolome of plant is crucial to optimize the evolution of crop traits, improve crop yields and qual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 92 publications
1
34
0
2
Order By: Relevance
“…In terms of tolerance for abiotic stresses such as water deficit, it is a tough plant however, for increasing demand of edible oil as well its vast pharmaceutical properties, its improvement seeks comprehensive understanding through omics. Omics by combining genomics, transcriptomics, proteomics and metabolomics (as solving a puzzle) attempts to obtain a clear picture of molecular and biochemical circuitries underlying primary and secondary metabolites/products 33 . In the same race, we tried to unravel an important class of transcription factors in Carthamus tinctorius L. Transcription factors express genes thus are essentially present in all organisms.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of tolerance for abiotic stresses such as water deficit, it is a tough plant however, for increasing demand of edible oil as well its vast pharmaceutical properties, its improvement seeks comprehensive understanding through omics. Omics by combining genomics, transcriptomics, proteomics and metabolomics (as solving a puzzle) attempts to obtain a clear picture of molecular and biochemical circuitries underlying primary and secondary metabolites/products 33 . In the same race, we tried to unravel an important class of transcription factors in Carthamus tinctorius L. Transcription factors express genes thus are essentially present in all organisms.…”
Section: Discussionmentioning
confidence: 99%
“…The safflower leaf extract presented a principal peak at retention time of 6.93 min, which was identified as a glycosylated flavonoid named luteolin 7-Oβ-D-glucoside, and with a common name of cynaroside. Other studies that have identified this compound in different anatomical parts of safflower were Kim et al (2006) in ethanolic seed extract, Mani et al (2020) in extract methanolic-water (80% v/v), in the extract of safflowers.…”
Section: Protective Effect On Human Erythrocytementioning
confidence: 99%
“…In addition, 200 mg/kg/d safflower yellow or hydroxysafflor yellow A in diet-induced obese mice can effectively inhibit fat mass by 57.8-61.6% [32]. Although it has been documented that safflower extract can be converted into substances in liver metabolism [3,4], the concentrations of either safflower extract or these compounds found in safflower extract in the blood and their half-life in the blood after administration are still unknown. In any case, the concentration of the compounds used in the in vitro experiment was similar to the dose used in this study [31].…”
Section: Discussionmentioning
confidence: 99%
“…The safflower extract is obtained from the dried flowers of Carthamustinctorius L., a plant of the Asteraceae family, by removing impurities, drying in the shade, or drying under low heat. Safflower is often used as a traditional Chinese medicine to promote hormone balance, remove blemishes, regenerate new cells, circulate blood, remove bruises, and relieve pain [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation